Panicle blast and canopy moisture in rice cultivar mixtures - Zhu, Youyong; Fang, Hui; Wang, Yunyue; Fan, Jin Xiang; Yang, Shi-Sheng; Mew, T.W.; Mundt, Christopher C. (Scientific Societies, 2005)
Glutinous rice cultivars were sown after every fourth row of a nonglutinous, hybrid cultivar in an additive design. The glutinous cultivars were 35 to 40 cm taller and substantially more susceptible to blast than was the nonglutinous cultivar. Interplanting of glutinous and nonglutinous rice reduced the incidence and severity of panicle blast on the glutinous cultivars by >90%, and on the nonglutinous cultivar by 30 to 40%. Mixing increased the per unit area yield of glutinous rice by 80 to 90% relative to pure stand, whereas yield of the nonglutinous cultivar was essentially unaffected by mixing. To determine whether the different plant heights and canopy structures may contribute to a microclimate that is less favorable to blast infection, we monitored the moisture status of the glutinous cultivars in pure stand and mixture at 0800 h by measuring relative humidity at the height of the glutinous panicles using a swing psychrometer and by visually estimating the percentage of leaf area covered by dew. Averaged over the two seasons, the number of days of 100% humidity at 0800 h was 20.0 and 2.2 for pure stands and mixtures, respectively. The mean percentage of glutinous leaf area covered by dewwas 84 and 36% for the pure stands and mixtures, respectively. Although other mechanisms also were operative, reduced leaf wetness was likely a substantial contributor to panicle blast control in the mixtures.